(3YdGL h UjGfI GdaNGQ GdeUGH HGdCedGM GdeMahX HeNRf GdHYHI GdCSJQGdjI HefWbI cQchQ (B- (3MdhGf (B: s (3JWHjbG Ydi HYV GdfeGPL GdeNJGQI (B/ s - (3eGLOg eMeO UGdMs; (3GdTjeGA YHOGdQMje YHOGdQMef (B: s; (3eMeO eUWai EHQGgje (B: s ((3GdbGgQI (B: s (3eGLOg eMeO UGdM (B: s, 2021)
(3JfGbT gPg GdQSGdI EMOi GdehVhYGJ GdgGeI HGdChGfi GdaNGQjI ef efWbI MdhGf (B((3eNRf cQchQ(B) (3YUQ eG bHd GdCSQGJ h GdYUQ GdYJjb(B: (3h cGf ddaNGQ CgejI ai GdeLehYI GdLfGFRjI ai YUQ eG bHd GdCSQGJ MJi GdOhdI GdMOjKI(B: (3h fJjLI dSRA GdOaf h YedjGJ GdMaX h GdJfNRjf ZjQ GdLjOI jUGH HGdCedGM(B: (3h efgG CedGM eJRgQI h CNQi eJHdhQI(B: (3h jfJL YfgG Jda GdaNGQ GdCKQi(B. (3dPG LGAJ GdQSGdI JMJ YfhGf(B: (3YdGL h UjGfI GdaNGQ GdeUGH HGdCedGM GdeMahX deMRf GdHYKI GdCSJQGdjI HefWbI cQchQ (B- (3MdhGf(B: (3JWHjbG Ydi HYV GdfeGPL GdeNJGQI(B. (3GdaUd GdChd(B: (3h jbY JMJ YfhGf(B: (3OQGSI JCKjQ GdGedGM Ydi GdCKGQ GdaNGQjI HefWbI MdhGf(B: (3h jfGbT efWbI CKGQ MdhGf (B((3eNRf cQchQ(B) (3h MaGFQ Rci SYO GdPi GSJWGY Cf jYKQ Ydi MdhGf(B: (3h HYO Pdc GSJced YdeGA CKQjhf CNQhf GdMaGFQ(B: (3Ke LGAJ GdHYKI GdCSJQGdjI dCSJceGd HGbi CYeGd MaGFQ Rci SYO(B: (3h OQGSI GdCedGM h eUGOQgG h CSHGH JchfgG Ydi GdChGfi GdaNGQjI h eSGejI GdaNGQ h MLe GdeSGe h GdJMce ai GdJHdhQ GdedMi(B. (3GdaUd GdKGfi h jbY JMJ YfhGf(B: (3GdaMhU h GdJMdjd ddChGfi GdaNGQjI ehVhY GdOQGSI(B: (3MjK Je CNP YjfGJ ef GdbWY GdeNJGQI(B: (3h GSJNOeJ GdYOjO ef WQb h GdJMdjd h GdMUhd Ydi fJGFL gGeI Je efGbTJgG h JMdjdgG h gi GdaMU GdHUQi h GdaMU HGSJNOGe GdejcQhSchH GdVhFi h GdejcQhSchH GdeSJbWH h GdJMdjd HMjhO GdCTYI GdSjfjI h GdJMdjd HGdJaGVd GdMQGQi(B: (3EVGaI Gdi bjGS GdJZjQ Gddhfis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdCKGQ (B- (3bSe GdJQejes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCedGMs; (3GdaNGQs; (3cdhQjO GdUhOjhes